Comparing doctor–elderly patient communication between traditional Chinese medicine and Western medicine encounters: Data from China. (1st November 2017) - Jin, Ying; Tay, Dennis
Abstract : Effective doctor–patient communication has been widely endorsed as pivotal for optimal medical care and the building of a positive and lasting relationship between caregivers and patients. While the literature suggests that traditional Chinese medicine (TCM) doctors have better interpersonal skills than Western medicine (WM) doctors, and that the doctor–patient relationship in TCM is more lasting, a comparison of specific communication behaviors in both encounters has not yet been carried out. This paper examines the similarities and differences in communication behaviors between these two types of consultations in relation to doctor–elderly patient communication. Forty-five consultations were included for analysis using the Roter Interaction Analysis System (RIAS). Significant differences were found in communication behaviors at the level of lifestyle and psychosocial exchanges, type of questions, non-medical small talk, and emotional disclosure. The study's limitations and implications are discussed.